Mangrove Density Analysis in Teluk Semanting Ecotourism Area using NDVI - Yusiyanti, Irma; Fadlullah Sam, Fathi; Muflichin Purnama, Syaiful (GEOID, 2025)
The mangrove ecosystem is of critical importance as a coastal vegetation system, playing a significant role in maintaining environmental stability, supporting social welfare, and fostering economic growth. In Teluk Semanting, Berau, East Kalimantan, mangrove forests play a vital role in preventing erosion, mitigating abrasion, providing habitats for various fauna, and supporting sustainable livelihoods through ecotourism. However, the area's mangrove forests are under threat due to the impact of human activities. To monitor mangrove forest development and prevent further degradation, it is essential to assess changes in the spatial distribution of mangrove land cover. This study utilises Sentinel-2A satellite imagery and the Normalized Difference Vegetation Index (NDVI) algorithm to analyse the spatial and temporal dynamics of mangrove cover in Teluk Semanting during the period 2019–2023. The results indicate a substantial decline in the high-density mangrove category, from 844.93 hectares in 2019 to 676.00 hectares in 2023, while the low- and medium- density categories exhibited a significant increase in area. This indicates a shift in mangrove quality from high-density to medium- and low- density categories. Regression analysis demonstrated a strong positive correlation (R² = 72.43%) between NDVI values and mangrove canopy density observed in the field, thereby underscoring the reliability of satellite imagery for monitoring mangrove conditions. The study emphasises the necessity of continuous monitoring and the implementation of conservation strategies to ensure the preservation of the ecological and economic benefits provided by mangrove ecosystems. This is particularly pertinent given the area's designation for ecotourism, where inadequate management could have adverse effects on the local community and global environmental stability.